2021
DOI: 10.3892/etm.2021.10918
|View full text |Cite
|
Sign up to set email alerts
|

Environmental allergens house dust mite‑induced asthma is associated with ferroptosis in the lungs

Abstract: Previous studies have indicated that allergens such as house dust mites (HDM) in the environment can induce allergic asthma. Ferroptosis is a newly discovered form of regulatory cell death characterized by aberrant lipid peroxidation and the accumulation of reactive oxygen species (ROS) in cells. However, whether ferroptosis participates in the pathological process of asthma remains to be elucidated. The present study used a HDM-induced mouse asthma model to determine the effect of HDM exposure on allergic ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…47 A recent study has shown that environmental allergens house dust mite-induced asthma is associated with ferroptosis in the lungs, and the effect of agonists and inhibitors of ferroptosis on airway inflammation in HDM-induced asthma also requires further study. 48 In our in vivo experiment, we found that HDM-induced mice treated with ferroptosis inhibitors (DFO and Fer-1) had decreased IL-4, IL-5 and IL-13 expression levels. The results indicated that inhibition of ferroptosis reduced type 2 airway inflammation in asthma.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…47 A recent study has shown that environmental allergens house dust mite-induced asthma is associated with ferroptosis in the lungs, and the effect of agonists and inhibitors of ferroptosis on airway inflammation in HDM-induced asthma also requires further study. 48 In our in vivo experiment, we found that HDM-induced mice treated with ferroptosis inhibitors (DFO and Fer-1) had decreased IL-4, IL-5 and IL-13 expression levels. The results indicated that inhibition of ferroptosis reduced type 2 airway inflammation in asthma.…”
Section: Discussionmentioning
confidence: 63%
“…Type 2 inflammation is an important disease mechanism in a large subgroup of individuals with asthma, and type 2 cytokines provided multiple potential therapeutic targets for asthma 47 . A recent study has shown that environmental allergens house dust mite‐induced asthma is associated with ferroptosis in the lungs, and the effect of agonists and inhibitors of ferroptosis on airway inflammation in HDM‐induced asthma also requires further study 48 . In our in vivo experiment, we found that HDM‐induced mice treated with ferroptosis inhibitors (DFO and Fer‐1) had decreased IL‐4, IL‐5 and IL‐13 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that IL13 is associated with mitochondrial dysfunction in patients with sialadenitis [ 14 ] and protects the mitochondria of cardiomyocytes in patients with septicemia [ 13 ]. Increased IL13 expression has been reported in the dysfunctional mitochondria of mice with house dust mite-induced asthma [ 17 ]. IL13 has been reported to increase the glucose tolerance and mitochondrial activity of the muscles after exercise [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL13 frequently accompanies mitochondria-related conditions, including in infectious disease [ 13 ], inflammatory diseases [ 14 ], and metabolic diseases [ 15 ] and even in cancers [ 16 ]. IL13 has also been reported to be associated with mitochondrial dysfunction in an animal-induced asthma model [ 17 ]. The relationship between blood leukocyte mitochondrial DNA copy number and inflammatory cytokines, including IL13, was also investigated in knee osteoarthritis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis was involved in the development and progression of a variety of lung diseases, including acute lung injury, COPD, and asthma [ 29 31 ]. Yoshida et al [ 32 ] investigated the involvement of ferroptosis in the development and progression of COPD both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%